2015
DOI: 10.1007/s00394-015-0976-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of digestive factors in determining glycemic response in a multiethnic Asian population

Abstract: Mastication parameters contribute significantly to GR. Eating slowly and having larger food boluses before swallowing (less chewing), both potentially modifiable, may be beneficial in glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 52 publications
1
49
0
Order By: Relevance
“…The minor (A) allele of SNP rs11185098 was reported to be positively associated with AMY1 gene copies (7). A higher number of AMY1 gene copies was associated with high salivary amylase activity in other studies (810), and three copy numbers of AMY1 and AMY2A have been shown to be numerically correlated (6). Therefore, the A allele of SNP rs11185098 was used in the current study as a marker of having high amylase activity.…”
Section: Methodsmentioning
confidence: 62%
See 2 more Smart Citations
“…The minor (A) allele of SNP rs11185098 was reported to be positively associated with AMY1 gene copies (7). A higher number of AMY1 gene copies was associated with high salivary amylase activity in other studies (810), and three copy numbers of AMY1 and AMY2A have been shown to be numerically correlated (6). Therefore, the A allele of SNP rs11185098 was used in the current study as a marker of having high amylase activity.…”
Section: Methodsmentioning
confidence: 62%
“…Previous studies reported that low AMY1 gene copies were associated with obesity (5,1214), although the findings were not consistent (7,15). Studies have shown that the AMY1 gene copy number is positively correlated with salivary amylase activity and serum amylase levels (810), and observational studies have consistently reported that low serum amylase concentrations are associated with obesity, insulin resistance, and metabolic abnormalities (1621,27). Studies linking AMY genotypes, amylase activity, and adiposity are still sparse, and the precise mechanisms underlying the current findings need further investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key determinants of the postprandial blood glucose response are the amount, rate and extent of carbohydrate digestion [4], insulin secretory response [5] and gastric emptying [6,7]. The extent of digestion, and thus the glycaemic response, are determined by the particle size of the food, the cooking method, the size of the mouthful, the extent of chewing and digestion that takes place in the mouth, and the physical and chemical properties of the starch [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…The key determinants of the postprandial blood glucose response are the amount, rate and extent of carbohydrate digestion [4], insulin secretory response [5] and gastric emptying [6,7]. The extent of digestion and thus the glycaemic response are determined by the particle size of the food, the cooking method, the size of the mouthful, the extent of chewing and digestion that takes place in the mouth, and the physical and chemical properties of the starch [8,9]. 2 of 12 One measure of a healthier cooked rice meal would be reduction of the glycaemic load (GL, i.e., slower and lower sustained release of glucose) by providing a lower proportion of rapidly digestible starch (RDS, starch that can be digested within 20 minutes following ingestion).…”
Section: Introductionmentioning
confidence: 99%